Effect of water pollution on esterases in Channa punctatus (Bloch) from Hussainsagar Lake, Hyderabad - Kumari, S Anitha; Kumar, N Sreeram (Indian Journal of Fisheries, 2011)
Electrophoretic analysis of liver and muscle tissues of Channa punctatus from non-polluted water bodies such as Osmansagar and Himayatsagar revealed that they contain six and eight esterase fractions respectively. Liver esterase consists of acetylesterase and carboxylesterases, whereas the muscle esterase is of three types, namely acetylesterase, carboxylesterase and cholinesterase. However, the liver and muscle tissue of Channa punctatus from polluted waters of Hussainsagar Lake showed only three fractions in liver and two in muscle, thus indicating inhibition under the impact of pollution.